Hubungan Antara Orientasi pada Kepuasan Konsumen dan Sistem Pemasaran Berbasis Syariah pada Usaha Kecil dan Menengah (UKM) di Banda Aceh - Alfian Anas (Universitas Teuku Umar, 2018)
Abstract: This study aims to investigate the relationship between customers’ satisfaction orientation towards implementing Islamic marketing in Small and Medium Enterprises (SME) through examining the dimensions of service quality and Islamic marketing. In order to achieve the study objectives, questionnaires were designed and distributed over 185 samples of SME entrepreneurs in Banda Aceh. The questionnaires were collected and analyzed by using the modified SERVQUAL model and analyzed with Cronbach Alpha and multiple regression analysis.The study concluded that service quality represented by tangibility, responsiveness, assurance, and empathy were positively related towards Islamic marketing, with the exception of reliability variable that did not have any effect on Islamic marketing. The results of this study will be useful for policy-making by authorities in Indonesia that are responsible for the development of SME sector, especially the Islamic marketing system. Future research is needed to study further on the readiness of the customers for a full-fledged of Islamic marketing implementation.